Decomposing employment growth in selected sub-Saharan African countries: The roles of structural changes and demographic transition - Abidemi C. Adegboye; Clement A. U. Ighodaro (CBN Journal of Applied Statistics, 2020)
The challenge of employment growth in SSA countries goes beyond economic growthprospects to include structural and demographic dimensions. This study examinesthe relative contributions of structural changes and demographic factors to employ-ment growth for a set of sub-Saharan Africa (SSA) countries using available annualdata from 1970 to 2014. A decomposition approach is employed in the study us-ing the Jobs Generation and Growth (JoGGs) method which generates results thatshow distributive components of employment, productivity and output changes overtime in a system whereby the roles of economic structure and demographic changescould be observed. The study shows that the pattern of structural change in SSAcountries has led to more low-productivity and vulnerable jobs generation. Ris-ing shares of the traditional services sector in the economy has driven a large seg-ment of employment into informal low-wage jobs. Major consequences of the natureof demographic changes in the SSA region are found to include decline in overallemployment rate and large movement of the labour market towards less produc-tive and low-wage employment. Social policies that address population and migra-tion are therefore required to ensure that demographic factors do not further inhibitavailability of productive employment in SSA.
Keywords: J4; J11; J62; O4; O17; 330; Decomposition; employment rate; output growth; productivity; sectoral shares